Analysis of Turbidity Test Bottled Drinking Water In Banyuwangi District - Pramesti, Dinda Sekar; Puspikawati, Septa Indra (Preventif : Jurnal Kesehatan Masyarakat, 2020)
Bottled drinking water (AMDK) is raw water that is processed, packaged and safe to drink (meets physical, chemical and bacteriological requirements) including mineral water and demineralized water. The physical requirements for drinking water quality include color, taste, turbidity and odor. The purpose of this study is to determine the turbidity of bottled drinking water circulating in Banyuwangi with the measurement method using a Turbidimeter. This is observtional research was conducted in April 2019 with 13 samples. The sampling technique used is purposive sampling. The average result of measurement of water turbidity level is 0.31 NTU, meaning that it meets the SNI 01-3553-2006 standard on Bottled Drinking Water so that it is safe to consume if viewed from turbidity parameters. Bottled Drinking Water is said to be feasible and safe to consume if it meets the requirements specified in SNI 01-3553-2006 concerning Bottled Drinking Water, which does not exceed the maximum threshold value that has been determined. Turbidity or turbidity of bottled drinking water (AMDK) originating from mountain springs raw water sources has a lower value compared to turbidity AMDK with groundwater raw water sources.